2015
DOI: 10.1210/en.2014-1685
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the GLP-1 Receptor by Liraglutide Increases ACE2 Expression, Reversing Right Ventricle Hypertrophy, and Improving the Production of SP-A and SP-B in the Lungs of Type 1 Diabetes Rats

Abstract: Diabetes alters microvascular function in the vascular beds of organs, including the lungs. Cardiovascular complications of pulmonary vascular affectation may be a consequence of the overactivation of the vasoconstrictive and proliferative components of the renin-angiotensin system. We previously reported that pulmonary physiology and surfactant production is improved by the glucagon-like peptide 1 receptor (GLP-1R) agonist liraglutide (LIR) in a rat model of lung hypoplasia. Because we hypothesized that strep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
125
0
11

Year Published

2016
2016
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 160 publications
(144 citation statements)
references
References 53 publications
4
125
0
11
Order By: Relevance
“…[42] Among other diabetic medications, the use of liraglutide and pioglitazone have also been found to be related with increased ACE2 regulation in animal studies. [42,43] The interconnection between ACE2, renin-angiotensin system (RAS) signalling, aging, DM, hypertension, and severity of COVID-19 may not be as simple as it may seem. As we described before, our meta-regression analysis showed that the association between DM and poor outcome was interdependent on age and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[42] Among other diabetic medications, the use of liraglutide and pioglitazone have also been found to be related with increased ACE2 regulation in animal studies. [42,43] The interconnection between ACE2, renin-angiotensin system (RAS) signalling, aging, DM, hypertension, and severity of COVID-19 may not be as simple as it may seem. As we described before, our meta-regression analysis showed that the association between DM and poor outcome was interdependent on age and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Study shows that activation of pulmonary ACE2 enzyme by a small synthetic molecule XNT (1-[(2-dimethylamino)ethylamino]-4-(hydroxymethyl)-7-[[(4-methylphenyl)sulfonyl]oxy]-9H-xanthene-9-one) prevents pulmonary hypertension and vascular remodeling, and suggests that pulmonary ACE2 may be a novel target for the successful control of pulmonary hypertension16. In addition of some studies showed activation of GLP-1 receptor by liraglutide increases ACE2 expression and preservation of GLP-1 is associated with a reduction of angiotensin II-induced cardiac fibrosis, and reversing right ventricular hypertrophy in type 1 diabetes rats2829. We conclude that liraglutide has a great potential as an anti-pulmonary hypertension drug.…”
Section: Discussionmentioning
confidence: 99%
“…However, propensity of thiazolidinediones to cause fluid retention and the risk of congestive heart failure in COVID-19 would make these agents unfavourable for treatment. Glucagon-like peptide-1 agonists have has been shown to increase ACE2 and increase surfactant in experimental animals [18]. Practical significance of changes in ACE2 levels with use of thiazolidinediones and glucagon-like peptide-1 agonists is not known.…”
Section: Anti-hyperglycaemic Drugs: Correct Selection and Potential Pmentioning
confidence: 99%